Mucoid Acinetobacter baumannii enhances anti-phagocytosis through reducing C3b deposition - Gong, Xiaoxia; Zhao, Qian; Wu, Yifan; Zhou, Hongwei; Ding, Shuangyang; Zhu, Kui (Frontiers in Medicine, 2022)
Background: Multidrug resistant (MDR) Acinetobacter baumannii causes serious infections in intensive care units and is hard to be eradicated by antibiotics. Many A.baumannii isolates are identified as the mucoid type recently, but the biological characteristics of mucoid A. baumannii and their interactions with host cells remains unclear. Methods: The mucoid phenotype, antimicrobial susceptibility, biofilm-forming ability, acid resistance ability, peroxide tolerance, and in vivo toxicity of clinical ICUs derived A. baumannii isolates were first investigated. Secondly, the phagocytic resistance and invasive capacity of A. baumannii isolates to macrophages (MH-S, RAW264.7) and epithelial cells (A549) were analyzed. Furthermore, the abundance of C3b (complement factor C3 degradation product) deposition on the surface of A. baumannii was investigated. Last, the relationship between C3b deposition and the abundance of capsule in A. baumannii isolates were analyzed. Results: These A. baumannii strains showed different mucoid phenotypes including hyper mucoid (HM), medium mucoid (MM), and low mucoid (LM). All tested strains were MDR with high tolerance to either acid or hydrogen peroxide exposure. Notably, these mucoid strains showed the increase of mortality in the Galleria mellonella infection models. Besides, the HM strain exhibited less biofilm abundance, higher molecular weight (MW) of capsule, and greater anti-phagocytic activity to macrophages than the LM strain. Together with the increased abundance of capsule, high expression of tuf gene (associated with the hydrolysis of C3b), the HM strain effectively inhibits C3b deposition on bacterial surface, resulting in the low-opsonization phenotype. Conclusion: Capsular characteristics facilitate the anti-phagocytic activity in hyper mucoid A. baumannii through the reduction of C3b deposition. Mucoid A. baumannii exhibits high phagocytosis resistance to both macrophages and epithelial cells. Keywords: A. baumannii; anti-phagocytosis; C3b deposition; capsule; mucoidity